Digital Marketing Capability and MSMEs Performance: Understanding the Moderating Role of Environmental Dynamism - Ika Purwanti; Dwi Reni Nisvul Lailyningsih; Umar Yeni Suyanto (Universitas Airlangga, 2022)
Objective: This study examines the influence of digital marketing capability on Micro, Small, and Medium Enterprises (MSMEs) performance. Environmental dynamism was the moderator in this relationship. Design/Methods/Approach: This study design was a quantitative approach. The research was conducted in Lamongan Regency. The research populations are managers or owners of MSMEs in the area. Using non-probability and purposive sampling techniques, this study reports the responses of 138 respondents from small and medium enterprises in Lamongan. Data were primarily gathered through self-reported online questionnaires. Partial Least Square (PLS) was then used to test the hypothesized relationships. Findings: The results show a positive effect of digital marketing capability on MSMEs performance and that environmental dynamism strengthens the relationship between digital marketing capability and MSMEs performance. Originality: Our study highlights the importance of focusing on digital marketing capability as a superior business strategy in responding to changes in consumer behavior. Empirical research on digital marketing capabilities in small-scale companies from the context of developing countries has not received serious attention (Chinakidzwa & Phiri, 2020b). To the best of our knowledge, this study is the first to link digital marketing capabilities to the MSMEs performance in Lamongan. Almost no previous research has examined environmental dynamism as a moderating role, especially in developing countries. Practical/Policy Implication: the owners or managers must focus on establishing and implementing the ability to apply digital marketing effectively. Digital marketing capability becomes one of the Company's strategic sources in creating competitive advantages, contributing to better business performance. An important practical implication of this research is that when MSMEs can adapt and transform digitally, they should concentrate on increasing digital marketing capability through activities such as providing product information on digital platforms, providing online services for customer needs, and building relations and communication with online consumers. Careful consideration of a firm's digital marketing capability is needed to improve business performance.